The Symbolic Interaction in Trumpets Playing During Worship Ceremony at Higher Than Ever Church - Agus Cahyono; Septian Cipto Nugroho; Wadiyo Wadiyo (Mudra Jurnal Seni Budaya, 2023)
The trumpet is an ancient instrument made of a sheep’s horn that is found in the Bible. In worship at the Higher Than Ever Church, the trumpet instrument is combined with modern musical instruments. Dealing with the background, the main focus of this study is related to symbolic interaction in the playing of Trumpet. The qualitative method using a research approach to the sociology of art approach was used in this research. The data obtained through observation, interviews, and documentation. Checking the validity of the data used source triangulation and data analysis used the contextualization of the synthesis model. The finding indicated that the symbolic interaction of playing the Trumpet started with Bible study activities, then it was conveyed to the congregation through the activity of Family Altar and other congregational activities, then after that the Trumpet instrument was played in the main worship ceremony. The conclusion has showed that symbolic interaction occurs between the Pastoral team and God through Bible study. Further, it is also between the Pastoral team and the leaders of the Family Altar, between the head of the Family Altar and church members, between the Trumpet players. Congregation and God when the worship ceremony is taking place.